KONSTRUKSI ALGORITMA PEWARNAAN TITIK PELANGI PADA GRAF POHON - Pranata, Widya Eka; Ibrahim, Irawan; Lamusu, Rizal; Syahrial, Syahrial; Abas, Mohamad Ilyas (Universitas Muhammadiyah Gorontalo, 2025)
This study constructs an algorithm for rainbow vertex coloring in tree graphs. A graph G is defined as a set pair G=(V,E), where V is the vertex set and E is the edge set. Rainbow dot coloring aims to assign a color to each vertex of a tree graph T, such that each path in the tree has vertices with unique colors. The rainbow dot coloring algorithm developed in this study is implemented in a programming language, and its performance is evaluated through simulations on various types of tree graphs. The results show that this algorithm can effectively color tree graphs with good optimality. This research contributes to graph coloring theory and its potential to be applied to computational problems involving tree graphs with complex structures.